PENGARUH GROWTH OPPORTUNITY, STRUKTUR MODAL DAN KEBIJAKAN DIVIDEN TERHADAP KEPUTUSAN INVESTASI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Maria Karolina Kewa; Gendro Wiyono (MANAJEMEN DEWANTARA, 2020)
This study aims to determine whether there is an influence of growth opportunities, capital structure and dividend policy on investment decisions in manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange (IDX) during the 2015-2018 period. The factors tested are growth opportunities, capital structure and dividend policy and investment decisions. The data used in this study are secondary data and this study uses 18 samples of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2018 period. This study uses the Social Sciences Statistics Package (SPSS) version 17.0 to determine the results of the hypothesis. Tests using SPSS get results that show that: 1) growth opportunities have a positive and significant influence on investment decisions; 2) capital structure has a positive and significant effect on investment decisions; 3) dividend policy has a negative and significant effect on investment decisions; 4) growth opportunity variables (company growth opportunities, capital structure, dividend policy simultaneously influence investment decisions.Kata Kunci: Incentives, Employee Discipline